2022
DOI: 10.1111/jocd.14802
|View full text |Cite
|
Sign up to set email alerts
|

Impact of IPL treatments on parameters of acne skin

Abstract: Background In the treatment of acne, skin parameters such as sebum secretion, hydration, and the content of hemoglobin and melanin are very important. The values of these parameters at the appropriate level show the maintenance of good functionality of the epidermal barrier and the impact of a given treatment procedure on the condition and physiology of the epidermis. Aims The aim of the study was to evaluate the effectiveness of anti‐acne therapy with IPL by volunteers, as well as to quantify parameters such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Mohame et al 32 studied 74 patients with acne vulgaris receiving IPL and half of the face with 1064‐nm Nd: YAG intervention and found a significant reduction in inflammatory acne at the end of treatment (67% and 70%) with no significant difference in efficacy between the two interventions ( p > 0.05). Zdrada et al 33 showed a reduction in sebum production and no significant changes in skin moisture loss, hemoglobin, or melanin levels in 27 patients with moderate‐to‐severe acne treated with four sessions of IPL, with a noteworthy satisfaction rate of 100% of treated patients. Enough to prove that IPL can reduce the number of propionibacterium acnes and the sebum excretion rate, thus exerting an anti‐inflammatory effect and improving skin texture.…”
Section: Discussionmentioning
confidence: 99%
“…Mohame et al 32 studied 74 patients with acne vulgaris receiving IPL and half of the face with 1064‐nm Nd: YAG intervention and found a significant reduction in inflammatory acne at the end of treatment (67% and 70%) with no significant difference in efficacy between the two interventions ( p > 0.05). Zdrada et al 33 showed a reduction in sebum production and no significant changes in skin moisture loss, hemoglobin, or melanin levels in 27 patients with moderate‐to‐severe acne treated with four sessions of IPL, with a noteworthy satisfaction rate of 100% of treated patients. Enough to prove that IPL can reduce the number of propionibacterium acnes and the sebum excretion rate, thus exerting an anti‐inflammatory effect and improving skin texture.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of IPL on rosacea may be related to selective photothermal effects and photobiomodulation [18][19][20][21]. Selective photothermal effects include targeting hemoglobin to destroy dilated blood vessels [11], reducing sebum secretion [22], and killing demodex [23]. Selective photothermal action is the principal theoretical basis of phototherapy; however, the photobiomodulation effect remains unclear, especially the effect of low-density IPL on rosacea.…”
Section: Introductionmentioning
confidence: 99%